Modelling of preconditioning by blasting in block and panel caving. (3rd April 2017) - Catalan, Alex; Onederra, Italo
Abstract: This paper discusses the results of design and modelling work conducted to estimate the extent of preconditioning from the effect of multiple explosive charges detonated simultaneously within typical block and panel caving layouts. The analysis was conducted to support existing and future implementation strategies of both conventional and higher intensity preconditioning by blasting. The work builds upon research previously published by the authors that concerned the modelling of fracturing, disturbed and interaction zones in confined blasting. In this instance, the Hybrid Stress Blasting Model was used to determine the disturbed and interaction zones for several scenarios involving 3–6 hole layouts. Modelling configurations were divided into two groups: (1) blastholes drilled from the undercut level, and (2) blastholes drilled from both the extraction and undercut levels. The first group considered four design patterns, with the analysis focusing on assessing whether a mining design layout of 32 × 20 m, using inclined holes were able to achieve positive interaction to increase the extent of preconditioning within the volume of interest. The second phase examined two designs where one and two additional holes are drilled from the extraction level in order to maximise the disturbed and interaction zones between blastholes. Variables such as the velocity of detonation; explosive density; intact rock mass strength and in situ the stress field were considered. Results indicated that the pattern that could maximise the extent of the disturbed zone and potential 'interaction' between blastholes was a six hole pattern drilled from both the undercut and extraction levels. This design is referred to as ' ultra blast preconditioning'. Further work is currently underway to quantify the costs and potential downstream productivity benefits of this particular scenario.